The palladium and copper contrast: a twist to products of different chemotypes and altered mechanistic pathways. Issue 9 (12th April 2016) - Seth, Kapileswar; Roy, Sudipta Raha; Kumar, Asim; Chakraborti, Asit K.
Abstract : Unprecedented Pd–Ag/Cu–Ag nanocluster-catalyst switch leads to a phenazine/azoarene twist for non-radical mode C–H activation vs. radical mode N–N self-coupling of anilines. Abstract : A novel contrast in palladium and copper catalysis is revealed to form products of different chemotypes resulting in a phenazine to azoarene twist through an altered mechanistic pathway (from non-radical C–H activation mode of C–N coupling to radical N–N coupling) during the oxidative self-coupling of anilines catalysed by Pd–Ag and Cu–Ag nanoclusters.